Importance Of Theoritical Basis In Teaching Listening - Islomova Maftuna Xazratkulovna; Kurbonova Gulmira Usmonovna, (European Journal of Life Safety and Stability (2660-9630), 2022)
The theme of this paper is demonstrating teaching listening on the basis of traditions of English-speaking countries part of the language at school. It is a practical teaching method that we apply to teach the learners with these methods. When learning a language, teaching and using the listening indicates every individual’s level in a certain language.